ADVERSE REACTION DUE TO CLINDAMYCIN - Thanusubramanian, Harish; Chogtu, Bharti; Magazine, Rahul (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT A 43-year-old patient was diagnosed of left sided empyema. He was started on injectable piperacillin-tazobactam combination and clindamycin. After 11 days, he developed itchy red lesions over different parts of the body. Both the drugs were immediately stopped in view of drug allergy. However, oral clindamycin with a lower dose was restarted, and patient tolerated the drug without any skin related episodes. Postdischarge he was prescribed oral clindamycin for 2 more weeks. 2 days postdischarge he started developing rash. The patient continued the drug for next 10 days and as a severity of rashes increased he reported to the hospital. He had itchy red lesions throughout the body. Clindamycin was stopped, and he was prescribed clonate lotion and tablet cetirizine for 10 days. The lesions resolved. A patient was informed that he is allergic to beta-lactams and clindamycin. Keywords: Clindamycin, Skin rashes, Beta-lactams.